Verbal and Non-Verbal Sign Found in Titanic Movie Poster - Darmayanti, Made Mei; Marantika, I Made Yogi (English Department, Faculty of Humanities, Andalas University, 2023)
The purpose of this study is to identify and analyze the verbal and nonverbal signs on the Titanic movie poster. It is expected to provide information about verbal and non-verbal signs and how they describe the content of that movie. This study used a Titanic Movie poster downloaded from Pinterest as the data source. The descriptive qualitative method was used by applying the Semiotic theory from Barthes (1997) to find out the verbal and non-verbal signs and to analyze the meaning of verbal and non-verbal signs on the Titanic Movie poster. Cerrato's (2012) theory of color meaning was used to support the analysis. In collecting data, there were several steps taken: select and download the movie poster for analysis on Pinterest, followed by reading and taking notes to recognize the posters. The findings indicate that there were 19 signs total, with I1 verbal signs and 8 nonverbal signs. The meanings of these signs were found in the words and pictures on Titanic Movie posters. In the verbal and non-verbal signs of the titanic movie poster, most of them conveys connotative meaning. In the non-verbal signs, almost all movie posters use photos of actors as models, it means the advertisement wants to attract public interest by using visuals of the actors playing the movie.